Chieti Document (2016) — Synodality and Primacy During the First Millennium - Матић, Златко (Sabornost - The Theological Year-book, 2016)
The author pays attention on the sixth document of the Joint Commission for theological dialogue between the Roman Catholic Church and the Orthodox Church. During the fourteenth plenary meeting (Chieti, Italia, September 16 to 21 2016), Commission published a document Synodality and Primacy during the first millennium: towards a common understanding in service to the unity of the Church, which contains some important practical and ecclesiological points of the present ecumenical search for full communion. The supplement brings the document translate in the Serbian language.